2005
DOI: 10.1055/s-2005-858109
|View full text |Cite
|
Sign up to set email alerts
|

New Optional IVC Filter for Percutaneous Retrieval - In Vitro Evaluation of Embolus Capturing Efficiency

Abstract: The new Celect filter showed similar in-vitro capture properties as the Gunther Tulip filter and deserves further in-vivo testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In addition, the newer model has eight thin secondary wires designed to stabilize and selfcenter the filter. 1,13 The modified filter is also more expensive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the newer model has eight thin secondary wires designed to stabilize and selfcenter the filter. 1,13 The modified filter is also more expensive.…”
Section: Discussionmentioning
confidence: 99%
“…Excess tilting can be a barrier to filter retrieval and may compromise filtration efficacy and, theoretically, pulmonary embolism prophylaxis. [1][2][3][4][5][6] Use of both filters is well described in the literature. [7][8][9][10] Initial studies have analyzed the retrievability of the modified filter and have demonstrated excellent results with reported retrieval rates Ͼ90%, which compares favorably with the older standard model.…”
mentioning
confidence: 96%
“…Some relied on only 10 trials for a single clot size; others combined trials from different setup parameters for each clot size, introducing variability not captured in the output statistic; others vary the number of trials without clearly defined justification. 21,2427,30,31 Using such small numbers of trials especially with the smaller clot sizes creates large standard error for binomial distributions. Assigning the number of trials to achieve a standard error of 5% as performed in this study ensured adequate number of trials to yield high confidence in the statistical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient we elected to use the Cook Celect™ IVC filter (Fig. 1), in preference to other retrievable filters because of its improved retrievability and comparable clot trapping ability 20–22 . It is a modification of the retrievable Gunther Tulip filter enabling for accurate centering of the filter within the IVC resulting in easier retrieval.…”
Section: Discussionmentioning
confidence: 99%